Assessing the Environmental Efficiency of Grain Production and Their Spatial Effects: Case Study of Major Grain Production Areas in China - Xu, Hanxiao; Ma, Bei; Gao, Qiang (Frontiers in Environmental Science, 2021)
Environmental factors have a profound impact on the evaluation of grain production efficiency. Taking environmental factors into account can more accurately measure grain production efficiency and judge the development position of grain production. Based on the global super-efficiency SBM model, environmental factors are included in the grain production efficiency measurement system, the temporal and spatial evolution characteristics of grain production environmental efficiency and the sources of inefficiency are analyzed, and the Spatial Durbin Model is used to investigate the influencing factors and spatial spillover effects of China's grain production environmental efficiency. The results show that: environmental factors have a significant impact on the efficiency of grain production in China; the environmental efficiency of grain production in China is fluctuating and decreasing; the environmental efficiency of grain production in different provinces has obvious spatial differentiation and geographical agglomeration; the main influencing factors of the environmental efficiency loss of grain production in major grain production areas are carbon emissions, non-point source pollution of grain production and labor input; the level of education, the level of technological development, and labor transfer have a significant positive spillover effect on the environmental efficiency of China's grain production, while the spatial spillover effect of the disaster rate is significantly negative. Grain production should pay attention to resource conservation and pollution control, strengthen cooperation and exchanges between provinces, and take the path of coordinated development between the environment and grain production.